Cryoelectrospun elastin-alginate scaffolds as potential cell delivery vehicles for mesenchymal stromal cell therapy - Pujhitha Ramesh; Rafael Pena; Jennifer M. Morrissey; Nicholas Moskwa; Kate Tubbesing; Xulang Zhang; Deirdre Nelson; James Castracane; Alexander Khmaladze; Susan T. Sharfstein; Melinda Larsen; Yubing Xie (Scientific Reports)
Abstract Salivary gland fibrosis results in salivary hypofunction whose current treatments are palliative. Mesenchymal stem/stromal cells (MSCs) are anti-fibrotic and anti-inflammatory and provide a promising alternative to treat fibrosis, but face translational challenges due to poor tissue targeting and retention. Scaffolds could facilitate targeted MSC delivery and improve MSC retention. Here, we demonstrated the feasibility of using stromal extracellular matrix (ECM)-mimicking elastin-alginate cryoelectrospun scaffolds (CES) for MSC delivery. Using MSC-like primary embryonic salivary mesenchyme cells (SMSCs), we demonstrated that CES supported viable, healthy and non-fibrotic long-term stromal cell maintenance while suppressing the fibrotic phenotype in myofibroblasts. We established an in vitro fibrosis model by coculturing SMSCs and myofibroblasts on CES and validated that SMSCs on CES imparted anti-fibrotic effects on myofibroblasts; however, these effects were suppressed by TGF-β1. In vivo orthotopic implantation of CES and SMSC-CES constructs showed that CES were biocompatible, non-inflammatory, and non-fibrotic, however, they did not remediate fibrosis. Further, supplementation of anti-fibrotic FGF2 to the in vitro fibrosis model demonstrated partial rescue of the anti-fibrotic effects of SMSC-CES constructs on myofibroblasts stimulated by TGF-β1 signaling. These studies set the premise for multi-pronged therapeutic approaches and validate CES as a potential stromal cell delivery vehicle in regenerative medicine applications.